Entrepreneurial skills to foster the employability of civil engineering students - Pagán Conesa, José Ignacio (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
Nowadays, recent graduates of civil engineering have problems finding their first employment despite the requirements of the degree. Creativity, collaboration and emotional intelligence are essential soft skills needed. Unfortunately, none of them appears in the civil engineering curriculum. This work proposes to conduct the creation of small cooperative teams of students to tackle different challenges. The collaborative resolution of problems from real-life situations and the presentation of the results is the key to the holistic development of future professionals. This research has shown the need for the development of soft skills to promote entrepreneurship and self-employment as job opportunities.